Grain-oriented electrical steel sheet and its manufacturing method
A tailored alloy composition and manufacturing process for grain-oriented electrical steel sheets, using Si, Al, Mn, N, P, S, Sb, C, Sn, Cr, Cu, and Mo, stabilize Goss texture, improving magnetic properties and reducing iron loss, thus enhancing power equipment efficiency.
Patent Information
- Application Number
- JP2024537315
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2022-12-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Existing methods for manufacturing grain-oriented electrical steel sheets face challenges in achieving high magnetic properties due to limitations in controlling grain growth inhibitors, leading to issues such as increased iron loss, poor cold rollability, and high production costs, while traditional alloying elements like boron, titanium, and selenium have limitations in effectiveness and cost.
A specific composition of alloying elements including Si, acid-soluble Al, Mn, N, P, S, Sb, C, Sn, Cr, Cu, and Mo, controlled within precise ranges, combined with a manufacturing process involving heating, hot rolling, cold rolling, and recrystallization annealing, to stabilize Goss texture and improve magnetic properties.
The solution results in a grain-oriented electrical steel sheet with improved magnetic permeability and reduced iron loss, achieving magnetic flux density of 1.90T or more and iron loss of 0.80W/kg or less, enhancing the efficiency of power equipment.
Smart Images

Figure 2024546166000001 
Figure 2024546166000002 
Figure 2024546166000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an electrical steel sheet, and more particularly to a grain-oriented electrical steel sheet and a method for manufacturing the same. [Background technology]
[0002] Grain-oriented electrical steel sheets have a texture of {110} <001> It exhibits a Goss texture and is a soft magnetic material with excellent magnetic properties in one direction or the rolling direction. To develop this texture, complex processes are required, including controlling the composition during steelmaking, controlling slab reheating and hot rolling process factors, annealing the hot-rolled sheet, cold rolling, primary recrystallization annealing, and secondary recrystallization annealing, and these processes must also be managed very precisely and strictly. During the process, it is also important to control the inhibitors, which are one of the factors that develop Goss texture. For example, grain growth inhibitors suppress the indiscriminate growth of primary recrystallized grains and allow only the Goss texture to grow during secondary recrystallization, a phenomenon that occurs when the inhibitor decomposes or loses its inhibitory power within the appropriate temperature range. To obtain Goss texture during final annealing, the growth of all primary recrystallized grains must be suppressed until just before secondary recrystallization occurs. To achieve this, the amount of growth inhibitor must be sufficiently large and uniformly distributed. Furthermore, because secondary recrystallization occurs during the high-temperature final annealing process, the inhibitor must have excellent thermal stability and not be easily decomposed.
[0003] The quality of grain-oriented electrical steel sheets is evaluated by magnetic flux density and core loss, and the more precise the Goss texture, the better the magnetic properties. Grain-oriented electrical steel sheets with excellent magnetic flux density and low core loss, as well as high quality, can be used to manufacture highly efficient power equipment, enabling the miniaturization and high efficiency of such equipment. To manufacture such high-quality grain-oriented electrical steel sheets, the Si content in the raw steel has been increased to reduce iron loss, but this has led to the problem of reaching the limits of cold rolling. To overcome this problem, attempts are being made to utilize siliconizing and to perform warm rolling by heating within an appropriate temperature range. Among the methods that utilize siliconizing, methods that siliconize steel sheets using chemical vapor deposition of SiCl4 gas or powder metallurgy require expensive capital investment for technological realization and make it difficult to achieve the target thickness due to the high silicon content.Technologies that perform warm rolling by heating within an appropriate temperature range require auxiliary equipment such as a heating furnace, making them uncommercially viable.
[0004] In addition, methods for improving the magnetic properties of electrical steel sheets include, unlike techniques that utilize the grain growth inhibitory effect of precipitates, a technique for increasing the fraction of Goss texture after secondary recrystallization high-temperature annealing by adding alloying elements that can obtain an inhibitory effect at a similar level to that of precipitates; a technique for increasing the fraction of Goss texture in the primary recrystallization texture during primary recrystallization annealing and increasing the fraction of secondary recrystallized fine grains in the Goss texture after secondary recrystallization high-temperature annealing; and a technique for uniformly distributing the size of the primary recrystallized crystal grains to prevent the growth of texture that is completely useless for improving magnetic properties due to the non-uniform structure of the primary recrystallization fine grains.
[0005] Among the above-mentioned technologies, the addition of boron (B) and titanium (Ti) to steel sheets has been proposed as a method of adding alloying elements to strengthen the weakened suppression of crystal growth caused by a single cold rolling process. However, boron is difficult to control at the steelmaking stage due to the small amount of addition, and after boron is added, coarse BN tends to form in the steel. Titanium also forms TiN or TiC, which have a solid solution temperature of over 1,300°C, and these remain even after secondary recrystallization, resulting in increased iron loss. The addition of selenium (Se) and boron (B) as grain growth inhibitors has been proposed, but the added boron is only effective when the steel contains an appropriate amount of nitrogen (N), and is ineffective if the nitrogen content is less than 10 ppm. Adding MnSe and Sb as grain growth inhibitors provides a high level of grain growth inhibition, resulting in high magnetic flux density, but weakens the material, making a single cold rolling impossible. If intermediate annealing is required, two cold rolling steps are required, increasing manufacturing costs. The use of expensive Se also increases manufacturing costs. One technique for inhibiting grain growth involves adding tin (Sn) and chromium (Cr) in combination, heating the slab at temperatures below 1,200°C, hot rolling, intermediate annealing, one or two cold rolling passes, decarburization annealing, and then nitriding using ammonia gas. However, this method requires strict control of the hot-rolled sheet annealing temperature based on the acid-soluble aluminum (Al) and nitrogen content of the steel, making the hot-rolled sheet annealing process complicated. Chromium (Cr), with its strong oxygen affinity, forms a very dense oxide layer during the decarburization nitriding annealing process, making decarburization and nitriding difficult. Furthermore, tin, a grain boundary segregating element, also makes decarburization and nitriding difficult. When copper (Cu) is added as a crystal growth inhibitor, molybdenum (Mo) merely serves to control the size of the precipitates caused by copper, but the tin and manganese content can also cause the precipitates to become coarse and uneven. Summary of the Invention [Problem to be solved by the invention]
[0006] The technical problem to be solved by the present invention is to provide a grain-oriented electrical steel sheet with improved magnetic properties by overcoming the limitations in improving magnetic properties. Another technical problem to be solved by the present invention is to provide a method for manufacturing a grain-oriented electrical steel sheet having the above advantages. [Means for solving the problem]
[0007] The grain-oriented electrical steel sheet of the present invention is characterized by containing, in weight percent, 2.0 to 6.0 wt% Si, 0.005 to 0.04 wt% acid-soluble Al, 0.01 to 0.2 wt% Mn, 0.01 wt% or less N, 0.0005 to 0.045 wt% P, 0.010 wt% or less S, 0.01 to 0.05 wt% Sb, 0.01 to 0.05 wt% C, 0.005 wt% or less Sn, 0.03 to 0.08 wt% Cr, 0.01 to 0.2 wt% Cu, 0.031 to 0.25 wt% Mo, and the remainder being Fe and other unavoidable impurities, and satisfying the following formula 1:
[0008] <Expression 1> 0.03<[Sn]<│√[Cu]+[Sb]-0.3 2 │ (In the above formula 1, [Sn], [Cu], and [Sb] represent the weight percentages of Sn, Cu, and Sb, respectively, √ represents the square root, and || represents the absolute value.)
[0009] The grain-oriented electrical steel sheet of the present invention satisfies the following formula 2.
[0010] <Expression 2> │√[Cu]-0.2│<0.3 (In the above formula 2, [Cu] means the weight percent of Cu, √ means the square root, and || means the absolute value)
[0011] The grain-oriented electrical steel sheet of the present invention has a magnetic permeability of 15,000 or more.
[0012] The method for producing a grain-oriented electrical steel sheet of the present invention comprises, in weight %, Si: 2.0 to 6.0 wt%, acid-soluble Al: 0.005 to 0.04 wt%, Mn: 0.01 to 0.2 wt%, N: 0.01 wt% or less, P: 0.0005 to 0.045 wt%, S: 0.010 wt% or less, Sb: 0.01 to 0.05 wt%, C: 0.02 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Cr: 0.01 to 0.2 wt%, Cu: 0.01 to 0.05 wt%, Sb: 0.02 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Cr: 0.01 to 0.2 wt%, Cu: 0.01 to 0.05 wt%, Sb: 0.02 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Sb: 0.01 to 0.05 ... The method includes the steps of: heating a slab containing 0.031-0.25 wt% of Ni, 0.01-0.05 wt% of Mo, and the balance being Fe and other inevitable impurities, and satisfying the following formula 1; hot-rolling the heated slab to produce a hot-rolled steel sheet; rolling the hot-rolled steel sheet obtained by heat treatment; primary recrystallizing the cold-rolled steel sheet obtained by cold rolling; and secondary recrystallizing the cold-rolled steel sheet that has undergone the primary recrystallization step.
[0013] <Expression 1> 0.03<[Sn]<│√[Cu]+[Sb]-0.3 2 │ (In the above formula 1, [Sn], [Cu], and [Sb] represent the weight percentages of Sn, Cu, and Sb, respectively, √ represents the square root, and || represents the absolute value.)
[0014] The step of reheating the slab is performed at 1,250°C or less. After the step of producing the hot-rolled steel sheet, the step of heat-treating the hot-rolled steel sheet may be performed at 1,000 to 1,150°C.
[0015] The method further includes a step of cold-rolling the hot-rolled steel sheet, followed by intermediate annealing the cold-rolled steel sheet that has been subjected to the first cold rolling, and a step of second cold rolling after the intermediate annealing.
[0016] The primary recrystallization step involves simultaneously performing decarburization annealing and nitriding on the cold-rolled steel sheet obtained by cold rolling, and the secondary recrystallization step is performed at a temperature of not less than 1,230°C and not less than the decarburization annealing temperature at which the primary recrystallization is completed. [Effects of the Invention]
[0017] By controlling the contents of antimony, tin, and copper, the grain-oriented electrical steel sheet of the present invention can simultaneously improve core loss and magnetic flux density, thereby providing a grain-oriented electrical steel sheet with excellent magnetic properties. Furthermore, the method for producing a grain-oriented electrical steel sheet of the present invention can produce a grain-oriented electrical steel sheet having the above-mentioned advantages. DETAILED DESCRIPTION OF THE INVENTION
[0018] Terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Therefore, a first part, component, region, layer, or section described below may be referred to as a second part, component, region, layer, or section without departing from the scope of the present invention. The terminology used herein is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the context clearly dictates otherwise. As used in the specification, the meaning of "comprising" embodies certain features, regions, integers, steps, operations, elements, and / or components, and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements, and / or components. When a part is referred to as being "on" another part, it can mean that it is directly on top of the other part, or there can be other parts between them. In contrast, when a part is referred to as being "directly on top of" another part, there are no other parts between them. Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention pertains. Terms defined in commonly used dictionaries are additionally interpreted to have a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted in an ideal or very formal sense unless otherwise defined.
[0019] Unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight.
[0020] In one embodiment of the present invention, the term "additionally containing an additional element" means that the remaining iron (Fe) is replaced by the additional amount of the additional element.
[0021] Although the present invention may be embodied in various different forms, it is not intended to be limited to the embodiments set forth herein, and the present invention is not limited to the embodiments set forth herein.
[0022] A grain-oriented electrical steel sheet according to an embodiment of the present invention contains, in weight percent, 2.0 to 6.0 wt% Si, 0.005 to 0.04 wt% acid-soluble Al, 0.01 to 0.2 wt% Mn, 0.01 wt% or less N, 0.005 to 0.045 wt% P, 0.010 wt% or less S, 0.01 to 0.05 wt% Sb, 0.005 wt% or less C, 0.03 to 0.08 wt% Sn, 0.03 to 0.08 wt% Sn, 0.01 to 0.2 wt% Cr, 0.03 to 0.25 wt% Cu, 0.01 to 0.05 wt% Mo, and the remainder being Fe and other unavoidable impurities.
[0023] The reasons for limiting the alloying components are explained below. Hereinafter, weight percent is expressed in percent. Si: 2.0 to 6.0%
[0024] Silicon (Si) is a basic component of electrical steel sheets, and plays a role in increasing the resistivity of the material and reducing core loss. The silicon content may be 2.0 to 6.0%. Specifically, the silicon content may be 2.0 to 5.0%. By satisfying this range of silicon content, the grain-oriented electrical steel sheet can stabilize the formation of secondary recrystallization, and can have excellent magnetic properties and workability.
[0025] If the silicon content is too high, excessive and dense SiO2 and Fe2SiO4 oxide layers form during decarbonitriding annealing, delaying decarburization. The phase transformation between ferrite and austenite continues during decarbonitriding annealing, severely damaging the primary recrystallization texture. Furthermore, the dense oxide layer retards decarburization, slowing nitriding. This prevents sufficient formation of nitrides such as (Al, Si, Mn)N and AlN, preventing sufficient grain suppression necessary for secondary recrystallization during high-temperature annealing. Even higher silicon content increases the mechanical properties of electrical steel, increasing brittleness and reducing toughness, increasing the incidence of sheet fractures during rolling. Furthermore, poor sheet-to-sheet weldability reduces ease of workability.
[0026] If the silicon content is too low, resistivity decreases, eddy current loss increases, and iron loss characteristics deteriorate. During decarbonitriding annealing, the phase transformation between ferrite and austenite becomes active, severely damaging the primary recrystallization texture. Furthermore, during high-temperature annealing, the phase transformation between ferrite and austenite not only makes the secondary recrystallization unstable, but also severely damages the {110} Goss texture.
[0027] Al:0.005~0.04wt%
[0028] Aluminum (Al) acts as a powerful grain growth inhibitor by forming finely precipitated AlN during hot rolling and annealing of hot-rolled steel sheets, as well as by combining nitrogen ions introduced by ammonia gas during the annealing process after cold rolling with Al, Si, and Mn present in solid solution in the steel to form nitrides in the form of (Al, Si, Mn)N and AlN. The aluminum content may be 0.005 to 0.04 wt%.
[0029] If the aluminum content is too high, coarse nitrides are formed, resulting in poor grain growth inhibitory effect, whereas if the aluminum content is too low, the number and volume of grain growth inhibitors in the form of (Al, Si, Mn)N and AlN nitrides are too low to be effective as grain growth inhibitors.
[0030] Mn:0.01~0.2wt%
[0031] Like Si, manganese (Mn) increases resistivity and reduces eddy current loss, thereby reducing overall iron loss. It also reacts with S to form Mn-based sulfides in the raw steel state, and reacts with Si and nitrogen introduced by nitriding to form (Al, Si, Mn)N precipitates, thereby suppressing the growth of primary recrystallized grains and promoting secondary recrystallization. Manganese can also react with S to form sulfide (MnS), which contributes to the formation, size, and dispersion of copper sulfide (CuS). The manganese content may be 0.01 to 0.2%.
[0032] Excessive manganese content can lead to the formation of large amounts of Fe2SiO4, (Fe, Mn), and Mn oxides on the surface of steel sheets, which can impede the formation of a base coating during high-temperature annealing and reduce surface quality. It can also induce a phase transformation between ferrite and austenite during high-temperature annealing, severely damaging the texture and significantly degrading magnetic properties. Furthermore, excessive manganese content, in conjunction with sulfur, can lead to the formation of very fine and excessive copper sulfides, which have an excessively strong inhibitor effect and prevent the secondary recrystallization of Goss-oriented crystal grains at the appropriate time. This can lead to excessively strong magnetic properties and problems with stable secondary recrystallization.
[0033] If the manganese content is too low, the number and volume of (Al, Si, Mn)N precipitates formed are small, resulting in a problem that sufficient effect as a grain growth inhibitor cannot be expected. Also, if the manganese content is too low, copper sulfides are formed coarsely and unevenly due to their relationship with sulfur, resulting in a problem that the inhibitor effect of copper sulfides is too small.
[0034] N: 0.01% or less
[0035] Nitrogen (N) is an important element that reacts with aluminum to form aluminum nitride (AlN). The additional nitrogen required to form nitrides such as (Al, Si, Mn)N, AlN, and (Si, Mn)N can be reinforced by nitriding the steel using ammonia gas during the annealing process after cold rolling.
[0036] The nitrogen content may be 0.01% or less. If the nitrogen content is too high, it can cause blisters, such as surface defects, due to nitrogen diffusion during processes after hot rolling, and excessive nitrides can be formed in the slab state, making rolling difficult and increasing the complexity of the process, and increasing the manufacturing cost.
[0037] C: 0.02 to 0.08%
[0038] Carbon (C) is an element that contributes to the refinement of grains by inducing a phase transformation between ferrite and austenite, thereby improving the elongation ratio. It is an essential element for improving the rollability of electrical steel sheets, which are highly brittle and have poor rollability. However, if carbon remains in the final grain-oriented electrical steel sheet, it causes carbides formed by the magnetic aging effect to precipitate in the steel sheet, thereby deteriorating the magnetic properties. Therefore, the final grain-oriented electrical steel sheet may further contain 0.01 wt.% or less of C. More specifically, it may further contain 0.005 wt.% or less of C.
[0039] The carbon content in the slab may be 0.02 to 0.08%. If the carbon content in the slab is excessively high, a sufficient decarburization effect cannot be obtained in the decarburization annealing process, which requires additional processes and equipment. In addition, since the decarburization effect is insufficient, the secondary recrystallization texture due to the phase transformation phenomenon is severely damaged, which causes a problem of deterioration of magnetic properties due to magnetic aging when the final product is applied to power equipment.
[0040] If the carbon content in the slab steel is too low, the phase transformation between austenite does not occur sufficiently, resulting in non-uniformity of the slab and hot-rolled microstructure, which in turn reduces the cold-rollability.
[0041] S: 0.010% or less
[0042] Sulfur (S) plays a role in suppressing grain growth by forming manganese sulfide (MnS) or copper sulfide (CuS) precipitates in the slab. The sulfur content may be 0.010% or less.
[0043] If the sulfur content is too high, sulfur segregates in the center of the slab during casting, preventing the uniform precipitation of manganese sulfide or copper sulfide in the subsequent hot rolling process, resulting in a non-uniform microstructure. Furthermore, if the sulfur content is too high, the formation of manganese sulfide or copper sulfide occurs unstably, making it difficult to control sulfides with tin (Sn) or antimony (Sb), as described below.
[0044] P: 0.0005 to 0.045%
[0045] Phosphorus (P) segregates at grain boundaries and prevents grain boundary migration. At the same time, it can play a supporting role in suppressing grain growth. <001> It has the effect of improving the texture. The phosphorus content may be 0.0005 to 0.045%.
[0046] If the phosphorus content is too high, the brittleness of the electrical steel sheet increases, resulting in poor rollability, whereas if the phosphorus content is too low, the effect of adding phosphorus to inhibit grain boundary migration and simultaneously inhibit grain growth is not realized.
[0047] Cr: 0.01 to 0.2%
[0048] Chromium (Cr) promotes the formation of hard phases in the annealed hot-rolled steel sheet, and thus the {110} Goss texture is formed during cold rolling. <001> By promoting the formation of Cr and accelerating the decarburization of carbon (C) during the decarburization annealing process, Cr plays a role in reducing the duration of the austenite phase transformation, thereby preventing the occurrence of a problem that can occur when the carbon content is high, which is a phenomenon in which the duration of the austenite phase transformation is prolonged and the texture is damaged. Chromium (Cr) also promotes the formation of a surface oxide layer during the decarburization annealing process, thereby overcoming the problem of the inhibition of oxide layer formation by tin (Sn) and antimony (Sb), which are alloying elements used as grain growth inhibitors. The chromium content may be 0.01 to 0.2%.
[0049] If the chromium content is too high, it promotes the formation of a denser oxide layer during the decarburization annealing process, which leads to poor oxide layer formation and hinders decarburization and nitriding. Furthermore, if the chromium content is too high, it is uneconomical because chromium is an expensive alloying element. If the chromium content is too low, it has little effect on reducing the austenite phase transformation maintenance time or resolving the problem of inhibited oxide layer formation.
[0050] Cu: 0.031 to 0.25%
[0051] Copper (Cu) not only promotes shear deformation during hot rolling and increases the proportion of Goss-oriented grains, but also forms sulfides, improving grain growth inhibition and increasing the concentration of Goss-oriented grains during secondary recrystallization. When sulfides are formed, copper sulfide may precipitate alone, but if manganese is present in the steel, it may also affect the precipitation of manganese sulfide, and if aluminum is present in the steel, it may also affect aluminum nitride.
[0052] Copper acts as a matrix for manganese sulfide and aluminum nitride while preferentially precipitating copper sulfide, and influences the behavior of manganese sulfide or aluminum nitride depending on the copper content. The copper content may be 0.031 to 0.25%.
[0053] Therefore, when copper is contained in an appropriate amount, secondary recrystallization is stabilized and the density of Goss-oriented crystal grains that have undergone secondary recrystallization is improved, thereby improving the permeability of the product sheet after high-temperature annealing.When copper is not contained in an appropriate amount, coarse and uneven precipitates are formed, which results in an uneven grain growth inhibition force, making the secondary recrystallization of Goss-oriented crystal grains unstable and reducing the density of Goss-oriented crystal grains that have undergone secondary recrystallization.
[0054] Specifically, if the copper content is too high, copper sulfides become excessively coarse, resulting in poor grain growth suppression, whereas if the copper content is too low, the targeted effect of increasing the fraction of Goss-oriented crystal grains is not achieved, and the effect on the precipitation of manganese sulfide and aluminum nitride precipitates is low.
[0055] Mo: 0.01 to 0.05%
[0056] Molybdenum (Mo) is a grain boundary segregating element. It has a relatively higher melting point than the base metal iron (Fe) and a very high melting point of about 2,600°C. Its strong ability to inhibit grain growth makes it an effective element for secondary recrystallization of Goss-oriented grains and for improving the density of Goss-oriented grains during high-temperature annealing. During hot rolling, it promotes shear deformation, thereby increasing the proportion of Goss-oriented grains in the hot-rolled texture. The molybdenum content may be 0.01 to 0.05%.
[0057] If the molybdenum content is too high, excessive segregation in the surface layer during the decarburization annealing process occurs, preventing the proper formation of an oxide layer and making the primary recrystallization microstructure too fine.If the molybdenum content is too low, the aforementioned effects of adding molybdenum are not realized.
[0058] Sb:0.01~0.05wt%
[0059] Antimony (Sb) segregates at grain boundaries and inhibits the growth of crystal grains and precipitates such as copper sulfide and manganese sulfide, resulting in fine precipitation, stabilizing secondary recrystallization. However, due to its low melting point, it easily diffuses and concentrates in the outermost surface layer during primary recrystallization annealing, preventing decarburization, oxide layer formation, and nitriding.
[0060] The antimony content may be 0.01 to 0.05%. Specifically, the antimony content may be 0.011 to 0.049%. Within this content range, copper sulfide and manganese sulfide are refined, which has the effect of strengthening the secondary recrystallization of Goss-oriented crystal grains. Furthermore, within this content range, the secondary recrystallization is stabilized and the density of the Goss-oriented crystal grains in which the secondary recrystallization has occurred is improved, which has been confirmed to improve the magnetic permeability of the product sheet after high-temperature annealing.
[0061] If the antimony content is too high, problems of decarburization, oxide layer formation, and nitriding due to nitriding become more serious, whereas if the antimony content is too low, the effect of refining sulfides does not appear.
[0062] Sn: 0.03 to 0.08%
[0063] Tin (Sn) is a grain boundary segregating element that prevents grain boundary migration and increases the proportion of Goss-oriented grains in the hot-rolled steel texture. Similarly to antimony, tin also has the effect of refining copper sulfide, manganese sulfide, and aluminum nitride, specifically, uniformly dispersing and precipitating sulfides. Furthermore, tin promotes the fine and uniform precipitation of aluminum nitride.
[0064] The tin content may be 0.03 to 0.08%. When the tin content satisfies this range, secondary recrystallization is stabilized and the density of Goss-oriented crystal grains resulting from secondary recrystallization is improved, thereby improving the magnetic permeability of the product sheet after high-temperature annealing.
[0065] If the tin content is too high, the grain growth suppression effect becomes too strong, preventing stable secondary recrystallization, whereas if the tin content is too low, copper sulfide, manganese sulfide, or aluminum sulfide precipitates coarsely and unevenly.
[0066] The balance is iron (Fe). Inevitable impurities may also be included. Inevitable impurities refer to impurities that are inevitably mixed in during the steelmaking and manufacturing processes of grain-oriented electrical steel sheets. Since unavoidable impurities are widely known, a detailed description of these impurities will be omitted. In one embodiment of the present invention, elements other than the above-mentioned alloy components may be added, and various elements may be included within a range that does not detract from the technical concept of the present invention. When an additional element is further included, it may be included as a substitute for the balance of Fe.
[0067] In one embodiment, the grain-oriented electrical steel sheet satisfies the following formula 1.
[0068] <Expression 1> 0.03<[Sn]<│√[Cu]+[Sb]-0.3 2 │ (In the above formula 1, [Cu], [Sn], and [Sb] represent the weight percentages of Cu, Sn, and Sb, respectively, √ represents the square root, and || represents the absolute value.)
[0069] The above formula 1 shows the relationship between copper and tin among the elements of grain-oriented electrical steel sheet. By satisfying the range of formula 1, there is an advantage that fine and uniform precipitates containing sulfide can be precipitated, but if the range of formula 1 is not satisfied, there is a problem that coarse and uneven precipitates containing sulfide can be precipitated, making it difficult to stably secure highly integrated Goss-oriented crystal grains.
[0070] In one embodiment, the grain-oriented electrical steel sheet can satisfy the following formula 2. <Expression 2>
[0071] │√[Cu]-0.2│≦0.3 (In the above formula 2, [Cu] means the weight percent of Cu, √ means the square root, and 11 means the absolute value.)
[0072] Equation 2 above is a relationship equation for the copper content of grain-oriented electrical steel sheet. By satisfying the range of Equation 2, secondary recrystallization is stabilized and the density of Goss-oriented crystal grains resulting from secondary recrystallization is improved, resulting in improved permeability of the finished sheet after high-temperature annealing. If the range of Equation 2 above is not satisfied, the copper content increases, resulting in excessive coarsening of copper sulfides, resulting in poor grain growth inhibition.
[0073] In one embodiment, the grain-oriented electrical steel sheet may have a magnetic permeability of 15,000 or more.
[0074] A method for manufacturing a grain-oriented electrical steel sheet according to another embodiment of the present invention includes the steps of heating a slab, hot-rolling the slab to manufacture a hot-rolled steel sheet, cold-rolling the hot-rolled steel sheet to manufacture a cold-rolled steel sheet, performing primary recrystallization annealing on the cold-rolled steel sheet, and performing secondary recrystallization annealing on the cold-rolled steel sheet after the primary recrystallization annealing.
[0075] First, the slab is heated. The alloy composition of the slab has been explained in relation to the alloy composition of the grain-oriented electrical steel sheet, so a duplicate explanation will be omitted. Specifically, the slab contains, in weight percent, Si: 2.0 to 6.0 wt%, acid-soluble Al: 0.005 to 0.04 wt%, Mn: 0.01 to 0.2 wt%, N: 0.01 wt% or less, P: 0.005 to 0.045 wt%, S: 0.010 wt% or less, Sb: 0.01 to 0.05 wt%, C: 0.03 to 0.25 wt%, Sn: 0.03 to 0.08 wt%, Sn: 0.03 to 0.08 wt%, Cr: 0.01 to 0.2 wt%, Cu: 0.03 to 0.25 wt%, Mo: 0.01 to 0.05 wt%, and the remainder consisting of Fe and unavoidable impurities.
[0076] Returning to the explanation of the manufacturing method, the slab can be heated to 1250°C or below. This allows the precipitates of Al-based nitrides and Mn-based sulfides to be incompletely or completely dissolved due to the chemical equivalent relationship between Al and N, and M and S, which are dissolved in solid solution.
[0077] Next, once the slab has been heated, it is hot-rolled to produce a hot-rolled steel sheet with a thickness of 1.0 to 3.5 mm.
[0078] After that, hot-rolled steel sheet annealing can be performed. In the hot-rolled steel sheet annealing step, the soaking temperature is 800 to 1300°C. If hot-rolled steel sheet annealing is performed, the non-uniform microstructure and precipitates of the hot-rolled steel sheet can be homogenized, but this step can also be omitted.
[0079] Next, the hot-rolled steel sheet is cold-rolled to produce a cold-rolled steel sheet. The cold-rolling step can be a single cold-rolling step or two or more cold-rolling steps including intermediate annealing. The thickness of the cold-rolled steel sheet is 0.1 to 0.5 mm.
[0080] Next, the cold-rolled steel sheet is subjected to primary recrystallization annealing. At this time, the primary recrystallization annealing step may include a decarburization step and a nitriding step. The decarburization step and the nitriding step may be performed in any order. For example, the decarburization step may be followed by a nitriding step, or the decarburization step may be performed after the nitriding step. In one embodiment, the cold-rolled steel sheet obtained by cold rolling may be subjected to decarburization annealing and nitriding treatment simultaneously to perform primary recrystallization. Specifically, the decarburization step and the nitriding step may be performed simultaneously. In the decarburization step, C may be decarburized to 0.01 wt % or less. More specifically, C may be decarburized to 0.005 wt % or less.
[0081] The nitriding step is for nitriding the inside of the steel sheet, and is a step of introducing nitrogen ions into the steel sheet, thereby precipitating precipitates such as (Al, Si, Mn)N or AlN, which act as grain growth inhibitors. Through the nitriding step, the nitrogen content of the grain-oriented electrical steel sheet can be nitrided to 0.01% or less.
[0082] In the primary recrystallization annealing step, the annealing temperature can be within the range of 800 to 950°C. If the annealing temperature is outside the upper limit of the range, the recrystallized grains grow coarsely, reducing the driving force for crystal growth and preventing stable secondary recrystallization. If the annealing temperature is outside the lower limit of the range, the decarburization takes an excessively long time.
[0083] The primary recrystallization annealing step is performed in a nitrogen, hydrogen, or a mixed gas atmosphere thereof. For example, the gas atmosphere may be an ammonia gas atmosphere. The gas atmosphere may be a wet atmosphere or a dry atmosphere.
[0084] After the primary recrystallization annealing step, an annealing separator may be applied to the steel sheet, for example, an annealing separator containing MgO as a main component. Annealing separators are widely known, so a detailed description thereof will be omitted.
[0085] Next, the cold-rolled steel sheet that has undergone primary recrystallization annealing is subjected to secondary recrystallization annealing. The purpose of secondary recrystallization annealing is to remove the {110} <001> The formation of texture and the formation of a glassy film due to the reaction between the oxide layer formed during the primary recrystallization annealing and MgO provide insulation and remove impurities that impair magnetic properties. The secondary recrystallization annealing method involves maintaining a nitrogen and hydrogen mixed gas atmosphere during the temperature rise section before secondary recrystallization occurs, protecting the nitrides that act as grain growth inhibitors and allowing the secondary recrystallization to develop well. After secondary recrystallization is complete, the soaking stage is maintained in a 100% hydrogen atmosphere for a long period of time to remove impurities.
[0086] The secondary recrystallization annealing step can be completed at a temperature of 900 to 1,250°C. Specifically, the secondary recrystallization annealing step can be completed at a temperature of 1,230°C or less.
[0087] The grain-oriented electrical steel sheet according to an embodiment of the present invention has particularly excellent core loss and magnetic flux density properties. The grain-oriented electrical steel sheet according to an embodiment of the present invention has a magnetic flux density (B8) of 1.90 T or more and a core loss (W 17 / 50 ) may be 0.80 W / kg or less. The magnetic flux density (B8) is the magnitude (Tesla) of the magnetic flux density induced under a magnetic field of 800 A / m, and the iron loss (W 17 / 50 ) is the magnitude of the iron loss (W / kg) induced under the conditions of 1.7 Tesla and 50 Hz.
[0088] Hereinafter, specific examples of the present invention will be described. However, the following examples are merely specific examples of the present invention, and the present invention is not limited to the following examples.
[0089] Examples 1 to 11 and Comparative Examples 1 to 6
[0090] Grain-oriented electrical steel sheets were vacuum melted to produce ingots, which were heated at 1,150°C and hot rolled to a thickness of 2.3 mm. The hot-rolled steel sheets produced by hot rolling were heated at 1,050°C and then quenched in water.
[0091] The annealed hot-rolled steel sheet was pickled and then cold-rolled once to a thickness of 0.23 mm. The cold-rolled steel sheet was subjected to simultaneous decarbonitriding annealing heat treatment by maintaining it at a temperature of 860°C in a humid atmosphere of a mixed gas of hydrogen, nitrogen, and ammonia for 200 seconds so that the nitrogen content was 180 ppm.
[0092] The cold-rolled steel sheets were coated with an annealing separator, MgO, and then subjected to final annealing, which was performed in a mixed atmosphere of 25% nitrogen and 75% hydrogen up to 1,200°C. After reaching 1,200°C, the final annealing was maintained in a 100% hydrogen atmosphere for 10 hours or more, followed by furnace cooling. Table 1 below shows the magnetic properties such as iron loss, magnetic flux density, and magnetic permeability, as well as the values of Equation 1 and Equation 2, for Examples 1 to 11 and Comparative Examples 1 to 6, depending on the Cu content.
[0093] The above formulas 1 and 2 are as follows: <Expression 1> 0.03<[Sn]<│√[Cu]+[Sb]-0.3 2 │ (In the above formula 1, [Cu] and [Sb] represent the weight percentages of Cu and Sb, respectively, √ represents the square root, and || represents the absolute value.)
[0094] <Expression 2> │√[Cu]-0.2│<0.3 (In the above formula 2, [Cu] means the weight percent of Cu, √ means the square root, and || means the absolute value)
[0095] [Table 1]
[0096] Looking at Table 1, when the Cu content is 0.03 to 0.23 wt%, the iron loss and magnetic flux density are significantly better than those of the comparative example, and the magnetic permeability is 15,000 or more, and it can be seen that there is also a significant difference in magnetic permeability.
[0097] Examples 12 to 23 and Comparative Examples 7 to 14
[0098] Grain-oriented electrical steel sheets containing 3.42 wt% Si, 0.063 wt% C, 0.005 wt% S, 0.005 wt% N, 0.029 wt% Sol-Al, 0.045 wt% Sn, 0.031 wt% P, 0.039 wt% Cr, 0.011 wt% Mo, and the remainder Fe and unavoidable impurities were vacuum melted, and then ingots were produced. These were then heated at 1,145°C and hot rolled to a thickness of 2.2 mm. The hot-rolled steel sheets produced by hot rolling were heated at 1,060°C and quenched in water.
[0099] The annealed hot-rolled steel sheet was pickled and then cold-rolled once to a thickness of 0.23 mm. The cold-rolled steel sheet was subjected to simultaneous decarbonitriding annealing heat treatment by maintaining it at a temperature of 870°C in a humid atmosphere of a mixed gas of hydrogen, nitrogen, and ammonia for 200 seconds so that the nitrogen content was 190 ppm.
[0100] The cold-rolled steel sheets were coated with an annealing separator, MgO, and then subjected to final annealing, which was performed in a mixed atmosphere of 25% nitrogen and 75% hydrogen up to 1,200°C. After reaching 1,200°C, the final annealing was maintained in a 100% hydrogen atmosphere for 10 hours or more, followed by furnace cooling. Table 2 below shows the magnetic properties such as iron loss, magnetic flux density, and magnetic permeability, as well as the values of Equation 1 and Equation 2, for Examples 12 to 23 and Comparative Examples 7 to 14, depending on the Sb and Cu contents.
[0101] [Table 2]
[0102] From Table 2, it can be seen that the examples in which the Sb content satisfies the range of the present invention have significantly superior magnetic flux density compared to the comparative examples, and show a significant difference in magnetic permeability of 15,000 or more.
[0103] Examples 24 to 35 and Comparative Examples 15 to 26
[0104] Grain-oriented electrical steel sheets were vacuum melted to produce ingots, which were heated at 1,150°C and hot rolled to a thickness of 2.2 mm. The hot-rolled steel sheets produced by hot rolling were heated at 1,040°C and then quenched in water.
[0105] The annealed hot-rolled steel sheet was pickled and then cold-rolled once to a thickness of 0.23 mm. The cold-rolled steel sheet after the cold-rolling step was subjected to simultaneous decarbonitriding annealing heat treatment by maintaining it at a temperature of 865°C in a humid atmosphere of a mixed gas of hydrogen, nitrogen, and ammonia for 200 seconds so that the nitrogen content was 200 ppm.
[0106] The cold-rolled steel sheets were coated with an annealing separator, MgO, and then subjected to final annealing, which was performed in a mixed atmosphere of 25% nitrogen and 75% hydrogen up to 1,200°C. After reaching 1,200°C, the steel sheets were maintained in a 100% hydrogen atmosphere for 10 hours or more, and then furnace-cooled. Table 2 below shows the magnetic properties such as iron loss, magnetic flux density, and magnetic permeability, as well as the values of Equation 1 and Equation 2, for Examples 24 to 35 and Comparative Examples 15 to 26, depending on the Sb and Cu contents.
[0107] [Table 3]
[0108] From Table 3, it can be seen that the examples in which the Sn content satisfies the range of the present invention have significantly superior magnetic flux density and permeability of 15,000 or more, showing a significant difference compared to the comparative examples.
[0109] As described above, it has been confirmed that in order to overcome the limitations in improving the magnetic properties of grain-oriented electrical steel sheets, it is possible to control the component system composed of alloying elements that can improve magnetic properties, specifically the component contents of alloying elements including Cu, Sb, and Sn.
[0110] The present invention is not limited to the above-described embodiments and / or examples, and can be manufactured in various different forms, and those skilled in the art will understand that the present invention can be embodied in other specific forms without changing the technical spirit or essential characteristics of the present invention. Therefore, it should be understood that the above-described embodiments and / or examples are illustrative in all respects and not limiting.
Claims
1. %. A grain-oriented electrical steel sheet satisfying the following formula 1, characterized in that it contains, in weight %, 2.0 to 6.0 wt % Si, 0.005 to 0.04 wt % acid-soluble Al, 0.01 to 0.2 wt % Mn, 0.01 wt % or less N, 0.0005 to 0.045 wt %, S: 0.010 wt % or less, 0.01 to 0.05 wt % Sb, 0.005 wt % or less C, 0.03 to 0.08 wt % Sn, 0.01 to 0.2 wt % Cr, 0.031 to 0.25 wt % Cu, 0.01 to 0.05 wt % Mo, and the balance being Fe and other unavoidable impurities. <Formula 1> 0.03 < [Sn] < │√ [C] + [Sn] - 0.03 2 │ (In the above formula 1, [Cu] and [Sb] respectively represent the weight percentages of Cu and Sb, √ represents the square root, and || represents the absolute value.)
2. 2. The grain-oriented electrical steel sheet according to claim 1, which satisfies the following formula 2: <Formula 2> │√[Cu]-0.2│<0.3 (In the above formula 2, [Cu] means the weight percent of Cu, √ means the square root, and ││ means the absolute value.)
3. 2. The grain-oriented electrical steel sheet according to claim 1, characterized in that the magnetic permeability is 15,000 or more.
4. %. In weight percent, it contains 2.0 to 6.0 wt % Si, 0.005 to 0.04 wt % acid soluble Al, 0.01 to 0.2 wt % Mn, 0.01 wt % or less N, 0.0005 to 0.045 wt % P, 0.010 wt % or less S, 0.01 to 0.05 wt % Sb, 0.02 to 0.08 wt % C, 0.03 to 0.08 wt % Sn, 0.03 to 0.08 wt % Cr, 0.01 to 0.2 wt % Cu, 0.031 to 0.25 wt % Mo, and the balance being Fe and other unavoidable impurities, Heating a slab that satisfies Equation 1 below: hot rolling the heated slab to produce a hot rolled steel sheet; cold rolling the hot-rolled steel sheet obtained by the heat treatment; A step of subjecting the cold-rolled steel sheet obtained by cold rolling to primary recrystallization; The method for producing a grain-oriented electrical steel sheet, comprising the step of subjecting the cold-rolled steel sheet that has been subjected to the first recrystallization step to a second recrystallization step. <Formula 1> 0.03 < [Sn] < │√ [C] + [Sn] - 0.03 2 │ (In the above formula 1, [Sn], [Cu] and [Sb] respectively represent the weight percentages of Sn, Cu and Sb, √ represents the square root, and || represents the absolute value.)
5. The method of claim 4, wherein the reheating of the slab is performed at a temperature of 1,250° C. or less.
6. After the step of producing the hot rolled steel sheet, heat treating the hot-rolled steel sheet; The method of claim 4, wherein the heat treatment of the hot-rolled steel sheet is performed at a temperature of 1,000 to 1,150°C.
7. The method of claim 4, further comprising the step of cold rolling the hot-rolled steel sheet and then intermediate annealing the cold-rolled steel sheet that has been subjected to the first cold rolling.
8. The method of claim 4, further comprising a secondary cold rolling step after the intermediate annealing step.
9. 5. The method of claim 4, wherein the step of performing the primary recrystallization comprises simultaneously performing decarburization annealing and nitriding treatment on the cold-rolled steel sheet obtained by cold rolling.
10. The method of claim 4, wherein the secondary recrystallization is performed at a temperature of not less than a decarburization annealing temperature at which the primary recrystallization is completed and not more than 1,230°C.
Citation Information
Patent Citations
Method for manufacturing grain-oriented silicon steel sheet having superior magnetic characteristic and film characteristic
JP2006274394A
Grain-oriented electrical steel sheet with excellent magnetic properties and method for manufacturing the same
JP2011510166A
Multipurpose cleaner
KR1020210118715A
Oriented electrical steel sheet and manufacturing method thereof
WO2020130328A1
